An Integrative Model for Educating Very Able Students In Rural School Districts - Peggy Detimer; Jean M. Lane (Educational Considerations, 1989)
A consulting teacher approach to educational programs for gifted students can offer enrichment opportunities to a broad range of the student population even as it provides the alternative learning environments very able students need in order to develop their potential.